A case of pediatric autoimmune neuropsychiatric disorder associated with streptococcal infection - R, Dr. Reshma; K, Dr. Ajnas (Indian Journal of Pharmacy & Drug Studies, 2024)
Pediatric autoimmune neuropsychiatric disease associated with streptococcal infection (PANDAS), is a subtype of acute-onset obsessive-compulsive disorder (OCD) induced by an immunological reaction to group A streptococcal infection. These diseases may be worsen by an autoimmune response brought on by streptococcal infections. One of the recurring diseases linked to PANDAS is recurrent streptococcal tonsillitis. "Strep throat" (acute suppurative tonsillitis) is a tonsil infection typically caused by Group A Beta-Hemolytic Streptococci (GABHS) bacteria, often leading to intense throat pain, fever, and difficulty swallowing for a few days. Health care providers frequently use a rapid strep test to check the tonsils of patients experiencing a sore throat for GABHS, as untreated infections can lead to more severe health issues. Occasionally, strep throat can result in a body rash (known as scarlet fever) and can also lead to more severe health issues such as arthritis in children, rheumatic fever that can cause long-lasting heart problems, and post-streptococcal glomerulonephritis which may result in kidney failure. Here we present a case of 20-year-old male patient with PANDAS, who underwent tonsillectomy. The morbidity associated with this neuropsychiatric condition can be reduced with prompt management.